1992
DOI: 10.3109/10428199209049798
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of the CD34 Antigen in Acute Myeloid Leukaemia

Abstract: The prognostic value of CD34 expression on leukaemic blast cells was assessed in 38 patients with acute myeloid leukaemia. Nineteen patients had more than 10% CD34 positive blast cells. Median survival for the CD34 positive patients was 125 days and for the CD34 negative patients the median survival has not yet been reached at day 575 (p = 0.06). Of those patients who received intensive chemotherapy, CD34 positive patients (n = 13) had a median survival of 150 days while for CD34 negative patients (n = 14) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 17 publications
2
17
0
1
Order By: Relevance
“…This is in agreement with CD34 expression as an indicator for poor response to induction therapy. [41][42][43] In addition, we demonstrate by multivariate analyses that NPM1 mutations are a strong independent favorable predictive marker for EFS, DFS, and OS in AML. The finding that the effect of NPM1 mutation is much more pronounced in multivariable than in univariable analyses can be explained by the strong correlation between NPM1 and FLT3 ITD mutations and additionally by the association with high WBC count and age.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with CD34 expression as an indicator for poor response to induction therapy. [41][42][43] In addition, we demonstrate by multivariate analyses that NPM1 mutations are a strong independent favorable predictive marker for EFS, DFS, and OS in AML. The finding that the effect of NPM1 mutation is much more pronounced in multivariable than in univariable analyses can be explained by the strong correlation between NPM1 and FLT3 ITD mutations and additionally by the association with high WBC count and age.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of the expression of particular antigens remains controversial with previous studies mostly focusing on single antigens [11][12][13][14]. In contrast, the influence of 3 immunophenotypic maturity of AML blasts on overall prognosis is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] For example, lymphoid-associated antigens such as CD19, CD7 have been considered adverse prognostic factors for AML patients, [6][7][8] as well as the increased expression of CD34 and bcl-2 protein. [9][10][11] More recently, several studies have addressed the role of CD56 expression in hematological malignancies. In fact, this antigen, an isoform of the neural adhesion molecules (NCAM), has been recorded not only in aggressive non-Hodgkin's T cell lymphomas, 15,16 but also in malignant plasma cells 33 and in several myeloproliferative disorders including acute leukemias.…”
Section: Figurementioning
confidence: 99%
“…[6][7][8][9][10][11] More recently, CD56 antigen, a 200-220 kDa cell surface glycoprotein, identified as an isoform of the neural adhesion molecules (NCAM) [12][13][14] was firstly described as a marker of natural killer cells and subsequently, has also been found expressed in several lympho-hematopoietic neoplasms including acute myeloid leukemias (AML). [15][16][17][18][19][20][21][22] In fact, it has been previously reported that in AML patients with t(8;21) (q22;q22), generally considered at lower risk of relapse, the presence of CD56 antigen on blast cells may influence complete remission (CR) duration and survival, 23 suggesting that CD56 expression could be useful in stratifying therapeutic approaches for this subtype of AML.…”
Section: Introductionmentioning
confidence: 99%